A comparative study of mechanical behaviour of heat-treated 3D printed In-718 and ASTM F75 alloys across multiple length scales - Zubair, Muhammad; Nur, Khushnuda; ul Haq, Ehsan; Ahmed, Furqan; Javed, Muhammad Adil; Khan, Muhammad Junaid; Naveed, Muhammad Mubeen; ul Hassan, Mirza Mueed; Abdullah, Ahmed (Journal of Mining and Metallurgy, Section B: Metallurgy, 2026)
The hardness and strength of many alloys often differ when measured at the nano, micro, and macroscopic scales. Therefore, it is essential to study the mechanical behavior of important alloys across a wide range of length scales. In this work, we present a scenario in which two industrially significant alloys, In-718 and ASTM F75, exhibit different behaviors at the micro and macroscopic levels. Both alloys are promising candidates for similar applications in the aerospace and petroleum industries. The alloys were first 3D printed using selective laser melting (SLM) and then heat-treated in a vacuum. The average yield strength and percentage elongation (along the build direction) of the In-718 alloy were 29% and 19% higher, respectively, than those observed for the ASTM F75 alloy. The difference between the ultimate tensile strength (UTS) and Vickers hardness (at a load of 98 N) was almost negligible, i.e., less than 5%. In contrast to the Vickers hardness values of 3.9 GPa and 3.8 GPa, the average nanohardness of the In-718 and ASTM F75 alloys was 5.7 GPa and 7.6 GPa, respectively, which was substantially higher than their Vickers hardness. Furthermore, the ASTM F75 alloy demonstrated much better wear resistance in ScanningWear tests performed using a nanoindenter. The explanation for these differences and the similarities between macro- and nanomechanical behavior are presented in this work.
Keywords: Mechanical properties; Nanoindentation; Mechanical behaviour; Alloys